Human Capital and Employee Performance : The Mediating Role of Training and Digital Innovation - Dini Istiqomah; Kasmari Kasmari (International Journal of Economics and Management Research, 2025)
The advancement of digitalization requires the Semarang City Population and Civil Registration Office (Disdukcapil) to improve employee performance through human resource management that adapts to technological developments. The implementation of digital-based services is essential to improving the efficiency and quality of public services. One innovation implemented is the Si D'nOK application, which has proven to accelerate and improve the issuance of e-KTP (electronic ID card) cards. This success demonstrates the critical role of digital innovation in supporting organizational performance. However, although employee training is believed to significantly contribute to strengthening human resource capacity and the success of innovations, empirical studies measuring the direct and indirect effects between human resources, training, digital innovation, and employee performance in the context of this agency are still limited. This study aims to analyze the influence of human resources on employee performance at the Semarang City Disdukcapil, with training and digital innovation as mediating variables. The approach used is a descriptive quantitative approach, with a survey method using a questionnaire distributed to all Disdukcapil employees. Data analysis was performed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) using SmartPLS 3 software. The results of the study indicate that human resources have a positive and significant impact on training, digital innovation, and employee performance. Training significantly impacts employee performance, and digital innovation has also been shown to contribute significantly to improved performance. Furthermore, human resources indirectly influence performance through improved training quality and the utilization of digital innovation.